Barriers to smoking cessation amongst people living with human immunodeficiency virus (HIV) in South Africa - Matsepe, Angela Morongwe (My University, 2022)
Background: Antiretroviral therapy (ART) coverage in South Africa has improved the quality of life of people living with the human immunodeficiency virus (PLWH). Smoking remains a major modifiable risk factor for non-HIV-related morbidity and mortality. The adverse effects of smoking continue to threaten the positive gains made by an effective ART programme. The prevalence of smoking is higher in PLWH than in their HIV-negative counterparts, yet, in subSaharan Africa, little is known about barriers to smoking cessation amongst PLWH. To address this gap in knowledge, we conducted a questionnaire study involving PLWH who attended an adult ART clinic in Johannesburg, South Africa. Objective: To describe barriers to smoking cessation for people living with HIV who attended the Chris Hani Baragwanath Academic Hospital Adult HIV Clinic in Johannesburg, South Africa. Methods: A voluntary, anonymous questionnaire was completed by 189 ARV (antiretroviral) clinic attendees; their demographic and smoking-related data was recorded. A Fagerström score was used to assess their level of nicotine dependence. Results: The mean age of people who completed the questionnaire was 45.4 years (standard deviation 11.77); 85.19% of participants were male. Overall unemployment was 65.61% and 70.31% had no matric qualification. The median number of years smoked was 19 (IQR 10–28 years) and the current median daily consumption was 6 cigarettes per day (IQR 4–10 cigarettes per day). The median Fagerström nicotine dependence score measure was 4 (IQR 2–5), which indicates low to moderate nicotine dependence. Overall, there were 179 (94.71%) individuals who were willing to quit smoking; the majority 134 (70.90%) of the total study participants had previously attempted to quit smoking. The majority of smokers (92.59%) were not familiar with smoking cessation pharmacotherapy. Of those who had previously attempted cessation, 69.40%) reported stress as a reason for failed previous attempts to quit smoking and 55.97% reported nicotine craving as another barrier to quitting. Overall, 36.51% of study participants reported concomitant alcohol use. Conclusions: An alarming number of PLWH were not familiar with smoking cessation modalities. Stress and nicotine cravings are some of the self-reported barriers to quitting smoking and, furthermore, concomitant alcohol use was reported. A significant majority of study participants reported a willingness to quit smoking, and this offers an opportunity to co-address smoking cessation during each ARV clinic follow-up visit, to educate attendees about the different modalities and to offer psychosocial support. In conclusion, smoking cessation measures that address the observed barriers are of great importance for the comprehensive management of HIV and AIDS in resource-limited countries, given the higher prevalence of smoking in PLWH, and the associated health risks.
A research report submitted in fulfilment of the requirements for the degree of Master of Science in Medicine to the Faculty of Health Sciences, School of Clinical Medicine, University of the Witwatersrand, Johannesburg, 2022